An Extended Home Visit Programme Within the Swedish Child Healthcare System for First-Time Parents in Scania, Sweden: A Study Protocol - Mangrio, Elisabeth; Hellström, Lisa; Nilsson, Eva-Lotta; Ivert, Anna-Karin (Frontiers in Public Health, 2021)
Background: The Swedish Child Health Care (CHC) system aims to provide equal and fair health care for all children and families in Sweden. Currently in Sweden, the CHC offers every family two home visits during the child’s first year of life, as well as extra home visits when there is a special need. Studies focusing on home visits show positive short- and long-term effects for first-time parents. During 2017, the Skåne Regional Council decided to initiate an extended home-visit program in the region of Scania for first-time parents. Instead of two home visits during the first year, a subsample of first-time parents would receive six visits during the child’s first 15 months. These six visits would be conducted by CHC nurses and social workers, midwives, and dentist-assistants. In the present paper, we describe a research project related to the regional extended home-visit program; the project aims to illuminate the experiences of the participants and to investigate the perceived health and social benefits of this program for both infants and parents. Method/analysis: In order to evaluate this intervention, three qualitative interview studies as well as one quantitative study with follow-up questionnaires will be conducted with first-time parents as the object of study. In addition, interviews with politicians, officials, and practitioners will be conducted in order to follow the implementation and experiences of the program from an organizational/administrative/governmental and professional perspectives. Discussion: Sweden has a well-established CHC program, but improvements are always possible. Previous research has shown that home visits are an effective tool to improve both the child’s physical and mental health as well as the parents’ well-being. However, this kind of intervention involves a significant investment from all organizations involved in the home visits; hence, it is important that the intervention is evaluated. The research project described in the present paper intends to examine the impact of the intervention, and its findings will aid decisionmakers in deciding the future of the home-visit program.